Uji Mutu Fisik Metoklopramid HCl Tablet Chewable dengan Variasi Jenis Pengisi sebagai Diluent menggunakan Metode Granulasi Basah - Latifiana, Umi; Budi Legowo, Deny; fitriany, erna; Priyoherianto, Andri; Novianto Ainul Huri, Muhammad (Jurusan Farmasi Universitas Negeri Gorontalo, 2021)
Metoclopramide HCl are used to reduce vomiting and nausea. The availability on the market in the form of tablet, syrup and injection. Patient tend to prefer take drugs by oral use because it was easier. Chewable tablet is the new product as the alternative ways to treatment children and adult patient who had difficulity problem of swallowing drugs. Objectives: This research aims to formulate the chewable metoclopramide HCl tablets using diluent variations to get a better physical quality test. Chewable tablets of metoclopramide HCl are made using diluent variations, they are mannitol, sucrose, lactose. Formula I mannitol, formula II sucrose, and formula III lactose. Chewable tablet preparations are made by the wet granulation method. Data collection was performed on physical characteristics including organoleptic, weight uniformity, uniformity of size, tablet hardness, tablet fragility, disintegration time, metoclopramide HCl levels. Physical quality test results were statistically analyzed to determine the effect of variations in the diluent on the characteristics of chewable tablets. The results of this research have an influence on the physical quality and uniformity of contents of various types of diluent variations between each formulation. In this research, fillers have an important role in the preparation of chewable metoclopramide tablets to determine the physical quality of the tablets and the uniformity of their contents. The variation of diluent that gives better results is mannitol. This is because formulas that use mannitol have uniformity in content that meets the requirements, faster disintegration time, and physical quality of tablets that still meet the requirements, when compared to the first and second formulations. The variation of diluent that gives better results is mannitol.